PENINGKATAN KOMPETENSI GURU DENGAN PEMANFAATAN ICT MELALUI APLIKASI PROTEUS DI SMK SETIA BUDI BALIKPAPAN - Maria Ulfah; Andi Sri Irtawaty; Hadiyanto .; Ali Abrar; Erick Sorongan (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
Based on the problems SMK Setia Budi Balikpapan related limitations of the amount of equipment supporting  Digital subjects, therefore the team PkM Balikpapan State Polytechnic community  service activities with the title "Improving Teacher Competence with ICT Utilization through Aplikai Proteus in SMK Setia Budi Balikpapan". PkM implementation methods include pre-test, introduction of Proteus application, Proteus application usage practice, followed by simulation test of learning practice along with monitoring (observation) to partner after PKM activity ends. The purpose of this activity can be achieved by increasing the competence of SMK Setia Budi's teachers  on Proteus Application so that it can be one alternative solution to overcome the limitations of the existing practicum tools especially for Digital Engineering subjects. And from the test results of learning practices from the students also helped to understand the learning materials with the use of this application.